Underwriter's Attributes and Their Relationship with IPO Underpricing - Ammer, Mohammed Abdullah Ezzi (2011)
Underwriting banks play a vital role in doing a successful initial public offering (IPO), which is considered as an important source of finance for Malaysian companies. This study aims to provide some evidence on the attributes of underwriters that affect the level of underpricing in IPOs in Malaysia. This evidence is on the application of IPO theories that are based on the information asymmetry between the IPO parties, issuing companies, underwriters, and investors. A total of 113 Malaysian IPOs listed from 29 June, 2006 until 24 February, 2011 were included in this study. For achieving the purpose of this study the OLS multiple regression technique was applied. In the multiple regressions, underpricing is used as the dependent variable and underwriter's reputation and spread as the independent variables while leverage, age, offer size, and company size were used as the control variables. The findings show that there is a negative significant relationship between reputation and underpricing. Also, the findings show that underwriter's spread has a positive significant association with underpricing. Besides that, the findings show the relationship between the control variables (leverage, age, offer size, and company size) and the dependent variable. One of these four control variables, leverage, has a positive significant relationship with IPO underpricing while the rest of these variables (age, offer size, and company size) have an insignificant negative relationship with IPO underpricing. Overall, evidence in this study supports the consensus of the existing international evidence that IPO underpricing increases or decreases following underwriting banks' attributes. These findings have implications for issuing companies, investors, and security analysts.